Partially Premixed Combustion (PPC) Stratification Control to Achieve High Engine Efficiency⁎. Issue 31 (2018) - Yin, Lianhao; Turesson, Gabriel; Yang, Tianhao; Johansson, Rolf; Tunestål, Per
Abstract: Partially premixed combustion (PPC) is a hybrid combustion of Homogeneous Charge Compression Ignition (HCCI) and Diesel Combustion (DC), which has a great potential in reducing the fuel consumption. PPC has a longer premixed time than DC but lesser than HCCI. Therefore it is more stratified than HCCI. This paper first presents results on how the stratification using multiple injections and different EGR influence the efficiency and proposes a control framework for PPC stratification control inspired from the experiments. The control framework is validated in transient operations. Results in both steady and transient operations demonstrated that the more stratified PPC with multiple injections has a lower fuel consumption.